Analisis Break Even Point dan Margin Of Safety Sebagai Alat Perencanaan Laba pada UMKM Bakmie Sultan Karawang - Oktavia, Dewi; Sihabudin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In principle, the main goal of every company is to achieve optimal profits for its owners. To be able to compete effectively with other companies, companies need to improve their operational performance more efficiently and effectively. Bakmie Sultan Karawang, a developing MSME business, still does not have accurate information regarding the profits generated from minimum sales of their noodles. This research aims to explore the role of Break Even Point (BEP) analysis in planning and increasing company profits. This research method uses a quantitative descriptive approach by applying BEP and Margin of Safety analysis techniques. The results of the break even point analysis show that the total business BEP reached Rp. 94,267,790.38, with details for each product Bakmie Komplit, Bakmie Bakso, Bakmie Pangsit, Bakmie Manis, and Bakmie Regular. Msargin of Safety (MOS) reached 93.03%, equivalent to Rp. 1,258,132,209.62, gives an idea of how much of a decline in sales can be handled without incurring a loss or breaking even. The estimated profit target for 2024 is 30%, or Rp. 177,263,404,629, which is a guide for the company in achieving the expected profit. Recommendations are provided so that companies can optimize BEP strategies to maintain sales above the break-even point and reduce potential losses. It is hoped that the results of this research will provide support for companies in designing optimal profit plans through BEP and MOS analysis.